Phytotherapy and food applications from Brassica genus. (5th March 2021) - Salehi, Bahare; Quispe, Cristina; Butnariu, Monica; Sarac, Ioan; Marmouzi, Ilias; Kamle, Madhu; Tripathi, Vijay; Kumar, Pradeep; Bouyahya, Abdelhakim; Capanoglu, Esra; Ceylan, Fatma Duygu; Singh, Laxman; et al.
Abstract : Plants of the genus Brassica occupy the top place among vegetables in the world. This genus, which contains a group of six related species of a global economic significance, three of which are diploid: Brassica nigra (L.) K. Koch, Brassica oleracea L., and Brassica rapa L. and three are amphidiploid species: Brassica carinata A. Braun, Brassica juncea (L.) Czern., and Brassica napus L. These varieties are divided into oily, fodder, spice, and vegetable based on their morphological structure, chemical composition, and usefulness of plant organs. The present review provides information about habitat, phytochemical composition, and the bioactive potential of Brassica plants, mainly antioxidant, antimicrobial, anticancer activities, and clinical studies in human. Brassica vegetables are of great economic importance around the world. At present, Brassica plants are grown together with cereals and form the basis of global food supplies. They are distinguished by high nutritional properties from other vegetable plants, such as low fat and protein content and high value of vitamins, fibers along with minerals. In addition, they possess several phenolic compounds and have a unique type of compounds namely glucosinolates that differentiate these crops from other vegetables. These compounds are also responsible for numerous biological activities to the genus Brassica as described in this review.